Implementation of Internet Network Load Balancing at the Faculty of Computer Science UNUSIDA Using the ECMP Method - Nida Aulina; Mochammad Machlul Alamin (Fakultas Teknik Universitas Bhayangkara, 2025)
A stable internet speed is essential in supporting worker and student task completion. Slow internet connectivity can become a persistent hindrance if it occurs continuously. Previous research indicates that conventional load balancing methods still have limitations in handling uneven traffic loads. This study, therefore, explores methods to optimize internet link utilization by distributing traffic load evenly, known as load balancing, using the Equal Cost Multi-Path (ECMP) method. This approach aims to maintain maximum data/packet flow, thereby preventing overload on a single link or connection failure. Testing was conducted by comparing network performance before and after ECMP implementation on two different ISPs. The test results showed that before implementing the ECMP method load balancing, the internet speed of ISP 1 was 29 Mbps, and the speed of ISP 2 was 16 Mbps. While after implementing load balancing using the ECMP method, the internet speed was 63 Mbps. Therefore, it is proven that implementing load balancing using the ECMP method can maintain and increase connection speed and share the load on both gateways so that overload does not occur.